Development of a Comprehensive Pavement Design System for Roads in Wind and Solar Farms - Santagata, Ezio; Sebaaly, Haissam; Capozzi, Vittorio (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
This paper briefly, illustrates the structure and contents of an ongoing research program aimed at developing a set of procedures and tools to be used for the design of pavements in renewable energy projects and mainly in wind and solar farms. Challenges related to this topic derive from the non-standard nature of several factors that affect the structural and functional performance of such pavements, with the consequent need of employing purposely defined prediction methods, design criteria and specifications. Further crucial aspects to be taken in account in the research program are related to the life cycle cost analysis of pavements, to be carried out in a multinational context by considering alternative scenarios according to an OPEX (operating expense) versus CAPEX (capital expenditure) philosophy. It is envisioned that results and deliverables of the project will contribute to the enhancement of the effectiveness of operations in wind and solar farms, optimizing investments and leading to the selection of more sustainable pavement solutions.